2005
DOI: 10.1002/pola.20708
|View full text |Cite
|
Sign up to set email alerts
|

Free‐radical polymerization of styrene with p‐nitrobenzyl triphenyl phosphonium ylide as an initiator

Abstract: The free‐radical polymerization of styrene with p‐nitrobenzyl triphenyl phosphonium ylide as an initiator in dioxane at 80 ± 1 °C in a dilatometer under a nitrogen atmosphere for 150 min resulted in a syndiotactic polymer, as evidenced by IR, 1H NMR, and 13C NMR spectroscopy. A 1H NMR spectrum showed methylene protons as triplets; 13C NMR signals of the phenyl ipso carbons were used for the determination of the tacticity. The system followed ideal kinetics. Gel permeation chromatography data were used evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The spectra for pure syndiotactic polystyrene generally contains sharp bands, as opposed to relatively broad bands obtained for atactic and isotactic polystyrene samples. 46 It has been reported that for pure syndiotactic 47 polystyrene the bands occur at 543, 739, 895, 1027, and 1200 cm -1 . In the present study the polystyrene sample showed sharp bands respectively at 546, 703, 766, 903, 1030, and 1177 cm -1 , indicating a component of syndiotactic behavior.…”
Section: Controlled Polymerization Of Styrene In Hbobmentioning
confidence: 99%
“…The spectra for pure syndiotactic polystyrene generally contains sharp bands, as opposed to relatively broad bands obtained for atactic and isotactic polystyrene samples. 46 It has been reported that for pure syndiotactic 47 polystyrene the bands occur at 543, 739, 895, 1027, and 1200 cm -1 . In the present study the polystyrene sample showed sharp bands respectively at 546, 703, 766, 903, 1030, and 1177 cm -1 , indicating a component of syndiotactic behavior.…”
Section: Controlled Polymerization Of Styrene In Hbobmentioning
confidence: 99%
“…We have successfully investigated homopolymerization14, 15 and copolymerization of vinyl monomers initiated by a phosphorus ylide. We therefore, have extended our studies to synthesize and characterize a terpolymer of St–MMA–AN initiated by a phosphorus ylide.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 One of the most common photocleavable protecting groups is the nitrobenzyloxycarbonyl (NBOC) group which degrades via a photoinduced intramolecular hydrogen abstraction, followed by thermal reactions which eventually yield, most often, an aldehyde and a carboxylic acid. 34,37 Nitro functionalities have been incorporated into polymers by postpolymerization modification, 35 free radical polymerization, [38][39][40] or ATRP 41 from an initiator containing a nitro group, and ATRP from p-nitrophenyl methacrylate, 42 but no examples of polymers prepared by ATRP that possess the NBOC functionality have been reported.…”
Section: Resultsmentioning
confidence: 99%